Water availibility of Karo Lake, Obi Island, South Halmahera - Nuraprianisandi Siska; Abfertiawan Muhammad Sonny; Gultom Tonny H.; Gunardi Petrus; Syahroni Muharwan (E3S Web of Conferences, 2024)
Lake Karo is one of the largest water sources on Obi Island. Obi Island has a large potential for water resources that can be used optimally by the local communities. This hydrological analysis purposed to calculate the water availability in Karo Lake. Water availability is the amount of water that is estimated to continue to exist in a location with a certain amount and within a certain period of time. Water availability is calculated by dependable discharge using the Mock method. The basis for the calculation of the Mock method is to calculate the rain that falls on the water catchment area, some will be lost as evapotranspiration, some will immediately become surface runoff and some will absorb into the ground (infiltration). The analysis used climate data, topography, and the area of the water catchment area in the watershed. In order to obtain an accurate dependable discharge calculation, it is necessary to have long-term rainfall monitoring data. The data used in the calculation of the Mock method is monthly rainfall data for the last 20 years from Rainfall Station data around the study location. The results of Digital Elevation Model data processing, the catchment area in the Lake Karo watershed is 65.11 km2. Based on the results of calculations using Mock method, the water availability in Lake Karo is always available year-round with a dependable discharge of Q80 is 1.8 m3/second. The water availability can be used for any purpose of the local communities.